Parametric Study of Applied Stresses on Infiltration Modular Cells Installed under Roads. (2016) - Aung, Tin Htoo; Khabbaz, Hadi; Fatahi, Behzad
Abstract: Modular geocellular units are applicable for the prevention and minimisation of stormwater runoff and flooding as a sustainable and cost-effective solution of road applications for drainage. The integrated units buried are exposed to the dead loads and live loads emerging from the surrounding soil pressure, pore water pressure and surcharge. Thus, a computer program using MATLAB is developed for the assessment of the total vertical and lateral earth pressure exerting on the modules complying with the Australian Standards AS 4678 (2002) and AS 5100.2(2004). Lateral earth pressure concept based on Rankine's theory is adopted in this model as the analytical approach. Closed-form solutions based on the fundamental soil mechanics are applied in the analytical calculation steps made. The model also considers different guidelines such as AASHTO LRFD Bridge Design Specifications (2010) for the stress distribution of vehicular loads according to the selected axle type. In consideration of the interaction of the moving vehicle and the bridge, the dynamic load allowance is also applied in terms of the static equivalent of the dynamic and vibratory effect as prescribed in AS 5100.2 (2004). Based on the results obtained, the numerical and theoretical results generated by the program provide considerable and influential factors in regarding to the parametric study and sensitivity analysis presented in this paper.